Development of E-Comic Teaching Materials to Improve the Learning Outcomes of IPAS Digestive System Materials for Grade V Students SD Negeri Pagerkukuh - Octaviani, Nur Fitria; Yulianto, Sigit (Jurnal Penelitian Pendidikan, 2026)
This research aims to develop e-comic teaching materials to improve the learning outcomes of IPAS digestive system material in class VA students of SD Negeri Pagerkukuh. The method used in this study is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The data collection instruments used include interviews, observations, questionnaires, and tests. Data analysis techniques include the feasibility and effectiveness of teaching materials. The research subjects consisted of teachers and students of the VA class of SD Negeri Pagerkukuh. The results of the study show that the e-comic teaching materials developed are declared very feasible to use based on the results of validation of material experts and media experts. The results of the questionnaire responses of teachers and students in small-scale trials and field trials were in the very good category. The effectiveness test showed an increase in learning outcomes as shown by the difference in pretest and posttest scores, and the results of the n-gain test can be concluded that e-comics teaching materials are quite effective in improving the learning outcomes of science of digestive system materials in grade V students of SD Negeri Pagerkukuh.